PENERAPAN KNOWLEDGE MANAGEMENT PADA PT. XYZ DENGAN MODEL SECI DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN - Wijaya, Mahaning Indrawaty; Gunawan, Ali (Universitas Negeri Surabaya, 2023)
This study aimed to analyze the running process of the knowledge management system at PT. XYZ and provide recommendations to the company to improve the knowledge management system in the company. Interviews and observations are done for data collection, which aims to understand user views and experience toward knowledge management systems and practices. Data processing was performed using the data triangulation method. A SWOT analysis is used to analyze all aspects of the knowledge management system in the company. The results of this study will help the company to make better decisions and improve its knowledge management system. This study also contributes to the literature on analyzing knowledge management systems using triangulation.